Construcción del ser mujer : el contraestereotipo femenino (2018)
The following investigation, researches the construction of being a woman in relation to the stereotypes present in the social context in which the participants are currently developing. The research was of a qualitative and descriptive nature, carried out in a natural context, through an interview about significant events in her life, perception of herself, concept of feminine stereotype and concept of being a woman, through her own history. Photography was used as a projection proposal, with it, we could know about the perceptions and sensations it created in her. And it was through the results obtained that conclusions were reached about the construction of being a woman and femininity today, through the emergence of counter-stereotypes